2011
DOI: 10.1007/s10924-011-0380-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Morphology, Chemical and Thermal Analysis of Cultivated Pineapple Leaf Fibres for Industrial Applications

Abstract: A study on chemical, morphology, and thermal analysis of cultivated pineapple leaf fibres (PALF) were carried out. The chemical compositions were determined by using Technical Association Pulp and Paper Industries standards. Fourier Transform-Infrared Spectroscopy analysis of PALF detect sharp band at 1,733 cm -1 , due to the absorption of carbonyl stretching of ester and carboxyl groups which is most abundant in pineapple leaf hemicelluloses. Cell wall ultra structure of PALF was studied by using Transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
(23 reference statements)
1
28
1
9
Order By: Relevance
“…Nadirah et al (2012) and Khalil et al (2006), for example, reported holocellulose content close to 80% and lignin content of 10.5%, values which are slightly inferior to those found in this study (Table 1). Furthermore, in a study of 12 pineapple leaf fiber varieties from Brazil, slightly inferior values to those found in the present work were also reported (Neto et al 2015).…”
Section: Evaluation Of Holocellulose Lignin and Extractives Contentcontrasting
confidence: 91%
See 1 more Smart Citation
“…Nadirah et al (2012) and Khalil et al (2006), for example, reported holocellulose content close to 80% and lignin content of 10.5%, values which are slightly inferior to those found in this study (Table 1). Furthermore, in a study of 12 pineapple leaf fiber varieties from Brazil, slightly inferior values to those found in the present work were also reported (Neto et al 2015).…”
Section: Evaluation Of Holocellulose Lignin and Extractives Contentcontrasting
confidence: 91%
“…In this study, the holocellulose was similar, but the lignin content was higher (15.45%). Finally, regarding the content of extractives in ethanoltoluene and NaOH solution, these were similar to those reported by Khalil et al (2006), Nadirah et al (2012), and Daud et al (2014) in Malaysia and Neto et al (2015) from the 12 Brazilian varieties. As shown in this study, the white-rot fungi degraded lignin in PALF (Isroi et al 2011).…”
Section: Evaluation Of Holocellulose Lignin and Extractives Contentsupporting
confidence: 87%
“…Oil Palm/Glass Polyester Oil palm/Sisal Natural rubber Jacob et al 2004a,b;Jacob et al, 2005;Jacob et al 2006a,b,c,d;Jacob et al 2007; Oil Palm/Jute Epoxy Jawaid et al, 2010;2011a-g;Khalil et al, 2011 Oil Palm/Kalonite Polyurethane Anuar and Badri, 2007 …”
Section: Hybrid Matrix Referencesmentioning
confidence: 99%
“…Research output show that dimensional stability, density, void content, and chemical resistance of oil palm EFB fibres reinforced epoxy composite improved with hybridization of oil palm EFB fibres with non woven/woven jute fibres (Jawaid et al 2011d,f,g;Abdul Khalil et al 2011). Hybridization of oil palm EFB composites with jute fibres improved physical properties of oil palm/jute hybrid composites due to packed and hybrid arrangement of fibre, less hydrophilic nature of jute fibres, better jute/epoxy interaction.…”
Section: Oil Palm/jute Fibre Reinforced Hybrid Compositesmentioning
confidence: 99%
See 1 more Smart Citation